2020
DOI: 10.5194/acp-20-2719-2020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ammonia on fine-particle pH in agricultural regions of China: comparison between urban and rural sites

Abstract: Abstract. Particle acidity is a fundamental property that affects atmospheric particulate chemistry. Synchronous online monitoring was performed at two urban sites, Zhengzhou (U-ZZ) and Anyang (U-AY), and three rural sites, Anyang (R-AY), Xinxiang (R-XX), and Puyang (R-PY) in Henan Province, during a haze episode to investigate the pH value and its driving factors in the agricultural regions of China. The pH values of particles calculated by ISORROPIA-II model at rural sites were slightly higher than those at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 64 publications
1
13
1
Order By: Relevance
“…Notably, the pH in spring (4.2 ± 0.7) was similar to the value found in urban Beijing (4.4 ± 1.2) in the same season. In comparison, the pH values in autumn and winter were 0.5 to 1.1 lower than those found in urban areas of northern China, such as 4.3 ± 0.8 in autumn in Beijing,2) in winter in Zhengzhou and 4.8 (3.9-5.9) in winter in Anyang (Ding et al, 2019;Wang et al, 2020). The higher LWC in urban areas may be one of the important reasons for its slightly lower acidity in autumn and winter compared to that in background areas in northern China.…”
Section: Seasonality Of Aerosol Aciditycontrasting
confidence: 54%
See 1 more Smart Citation
“…Notably, the pH in spring (4.2 ± 0.7) was similar to the value found in urban Beijing (4.4 ± 1.2) in the same season. In comparison, the pH values in autumn and winter were 0.5 to 1.1 lower than those found in urban areas of northern China, such as 4.3 ± 0.8 in autumn in Beijing,2) in winter in Zhengzhou and 4.8 (3.9-5.9) in winter in Anyang (Ding et al, 2019;Wang et al, 2020). The higher LWC in urban areas may be one of the important reasons for its slightly lower acidity in autumn and winter compared to that in background areas in northern China.…”
Section: Seasonality Of Aerosol Aciditycontrasting
confidence: 54%
“…This difference of MO-OOA formation between urban and background sites in the NCP was mainly due to the higher atmospheric oxidation capability in the background atmosphere than in the urban atmosphere in summer. A previous study showed that O x concentration at the background sites was 30 % higher than that at the urban site during summertime (Wang et al, 2013). Furthermore, increases in LO-OOA and MO-OOA as functions of O x were clearly associated with the increases in wind speed in Xinglong, which were more significant in summer than in other seasons.…”
Section: Evolution and Formation Of Soamentioning
confidence: 76%
“…Higher PM 2.5 pH values (around 2 to 3) were reported for Los Angeles during the CalNex campaign due to higher aerosol water concentrations, which was a result of higher total NO 3 − concentrations and NO 3 − -HNO 3 partitioning [5]. Locations close to areas with intensive agricultural activities that emitted high levels of NH 3 (e.g., parts of mainland China and Europe) had fine pH values as high as 6 [14,36,37]. Higher fine aerosol pH values (around 4 to 6) were reported for urban areas impacted by sea salt (e.g., San Paulo, Hawaii) and dust (e.g., Inner Mongolia, Po Valley) due to the neutralizing effect of NVCs [14,[38][39][40][41].…”
Section: Introductionmentioning
confidence: 81%
“…Sulfate, an important component of atmospheric secondary inorganic aerosols, plays an important role in the formation of haze (Wang et al, 2014;Yue et al, 2019). The correlation coefficient (R 2 ) between the measured IC-SO 2− 4 and ACSM-SO 2− 4 was only 0.26 for IAP with a slope of 0.54.…”
Section: Comparison With Tof-acsm Datamentioning
confidence: 99%